ANALISIS VEGETASI DI PULAU BINTAN, KEPULAUAN RIAU - Pratama, Bayu Arief; Mirmanto, Edi (BERITA BIOLOGI, 2019)
Ecological study with special attention to vegetation analysis has been done in the Bintan forest area, Riau Archipelago. Based on three sampling plots of 30 × 30 m, there were 73 tree (dbh ? 5 cm) species were recorded, belong to 64 genera and 32 families. The density is fairly high (1,485 individuals /ha) with total basal area relatively low (27.71 m2/ha).  Its indicates that most of trees are small size. Similarity index among study sites are relatively low (< 25 %), indicates that there is strong relation between habitat and species composition. Out of the 6 most common tree species in the study area, only Dipterocarpus gracillis was dominant in 2 study sites. Overall species diversity is relatively low, which is characteristic of forest vegetation on small islands.